2014
DOI: 10.1016/j.foodqual.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Combining experimental auctions with a modified home-use test to assess rural consumers’ acceptance of quality protein maize, a biofortified crop

Abstract: Biofortification, or breeding food crops for improved nutritional content, is a cost effective way to improve nutritional status. The process can, however, alter the sensory characteristics of the crop, and consumer acceptance is essential for their adoption. The oldest biofortified crop is quality protein maize (QPM), biofortified with essential amino acids, now found in many recently-released varieties in East Africa. To estimate rural consumers' acceptance and willingness to pay (WTP) for QPM in the dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
5
34
0
Order By: Relevance
“…The experience of this study showed how BDM, which is conducted individually, was easy to use with respondents with little or no education, and particularly suited for rural dispersed populations. It was therefore selected to estimate WTP for quality protein maize, in combination with both central locations affective tests and modified home use tests, with adults and with both mothers and children, with all experiments including an information component.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experience of this study showed how BDM, which is conducted individually, was easy to use with respondents with little or no education, and particularly suited for rural dispersed populations. It was therefore selected to estimate WTP for quality protein maize, in combination with both central locations affective tests and modified home use tests, with adults and with both mothers and children, with all experiments including an information component.…”
Section: Methodsmentioning
confidence: 99%
“…They were asked to provide a score on a five‐point hedonic scale for different sensory attributes (dislike very much, dislike, neither like nor dislike, like, like very much). The five‐point scale is much easier to use by enumerators interviewing consumers with limited or no education than the standard nine‐point scale, which is typically used by consumers filling in the response sheets themselves, and has been used in several recent consumer studies in Africa . The sensory traits used were appearance, aroma, texture in hand, flavour, texture in mouth, taste and overall appreciation (not an average, but a separate overall evaluation).The products were identified with a neutral symbol, randomly assigned (A, circle; B, square; C, triangle; D, diamond; E, rectangle) (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in dispersed rural populations, BDM is sometimes preferred over other auction mechanisms, as it allows for eliciting valuations from individuals (home-use testing) and because carrying out group auctions (central-location testing) can be expensive and time-consuming. 39 Another reason is that laboratory auctions may require higher participant fees, which have shown to positively affect valuations, [40][41][42] a phenomenon known as an income endowment effect. 43 Such monetary incentives may be of particular relevance when considering students rather than adults, 44 despite the fact that both types of respondents, commonly targeted in WTP research, are not expected to bid significantly differently.…”
Section: Introductionmentioning
confidence: 99%
“… A process in which micronutrient contents of crops are increased through biotechnology or conventional plant breeding (De Groote et al ., ). …”
mentioning
confidence: 97%